La Logique subjective - Hegel, Georg Wilhelm Friedrich, 1770-1831 (Livre numérique., 2015)
Excerpt: " The materials contained in that part of philosophy which will now occupy us are the same that we find in most of logic treaties. But in my system, it must be remarked, they are closely related to any that is generally referred to by other names; "